Custos de mudança e seus impactos na falsa lealdade, nas emoções negativas e comunicação boca-a-boca de consumidores de telefonia celular - Kamila Tôrres Madureira (2012)
ln some cases consumer and companies desire to be in a stable and confident relationship in the long term, without have to keep moving the providers or the eostumers, Sometimes companies act in a way to maintain customers without provide benefits that justify the stay, as can happen in the pospaid cell phone sector. So, the question that arises is switching costs are pereeveid by the pos-paid cell phone consumer to change thc provider and what impacts they have in a negative outcomes to companies? Thus, this study aimed to determine the direct relationship between the switching costs to change pos-paid cell phone provider, false loyalty, negative emotions and negative word of mouth, To achieve this goal, a cross section conclusive descriptive study was conduct, including a qualitative and quantitative phases, in individuals over 18 years, residing in Belo Horizonte city, that have mobile post-paid no corporate code 31. Based on the qualitative phase were identified nine switching costs in the speech of those interviewed who were Evaluation costs, Attractiveness of alternatives, Econornie risk, Learning costs, l\/lonetary loss, Relationship with the company, Setup costs, Contract termination and Benefits loss costs. Based on the results from this phase and the literature was constructed a questionnaire that was previously tested and applied, and validated at the end were 400 (enough to test the model). The rnodcl tested in the quantitative phase was statistically significant and showed that the cost of Relationship with the company and Evaluation confirmed the hypotheses regarding the construct False Loyalty. The other seven costs rejected the hypothesis, while Economic risk and Monetaryl loss showed an impact statistically significant contrary to the expected. The results showed that in the case of Negative emotions the irrrpact of the constructs Evaluation, Relationship with thej company, Setup costs, Contract termination, and False Loyalty confirmed the previously established hypotheses. The others five costs did not present a result as was expected by the hypothesis and the Econornie risk also presented contrast to the hypothesized value. lt was also noted that the higher the False loyalty and more frequent the consumers feel negative emotions, is greater the tendency for content communicated is negative. On the other hand, the False loyalty showed no impact on the Frequency of communication and the Number of people who received the communication, while the more iitequent the perception of negative emotions with more people and more often the consumer tell about the company to others